2011
DOI: 10.1016/j.yebeh.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of placebo effect of repetitive transcranial magnetic stimulation in epilepsy

Abstract: Objective-Low-frequency repetitive transcranial magnetic stimulation (rTMS) is emerging as a therapeutic tool in epilepsy. In recent years, several open-label trials have shown an encouraging reduction in seizure frequency in patients with epilepsy. However, the data from controlled trials are mixed with respect to antiepileptic rTMS efficacy, and the field would benefit from further carefully controlled trials. Prior to initiating new trials, it is important assess the magnitude of the placebo effect of prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Moreover, sham rTMS has been shown to have the potential for a low but detectable placebo effect. 35 Although both rTMS QP ( present data) and training 36 modalities can facilitate descending corticospinal pathways after neurologically-incomplete SCI, the functional outcome appears to be greater when two modalities (i.e. inputs) are combined, supporting the "more is better" concept.…”
Section: Alexeeva and Calancie Efficacy Of Quadropulse Rtms For Impromentioning
confidence: 55%
“…Moreover, sham rTMS has been shown to have the potential for a low but detectable placebo effect. 35 Although both rTMS QP ( present data) and training 36 modalities can facilitate descending corticospinal pathways after neurologically-incomplete SCI, the functional outcome appears to be greater when two modalities (i.e. inputs) are combined, supporting the "more is better" concept.…”
Section: Alexeeva and Calancie Efficacy Of Quadropulse Rtms For Impromentioning
confidence: 55%
“…Additionally with regard to placebo design, the relevance must be interpreted within the context of individual experimental findings. Previous investigators have compared tilting the coil at 90 degrees, similar to our method, and found that it is not to be inferior to a commercially available Magstim sham coil (Magstim, Whitland, UK) [8]. It has also been estimated systematically in TMS studies for epilepsy that the placebo effect, even with this orthogonal coil position, was similar to spring loaded or double active sham coils at 0% to 2% only [9].…”
Section: Discussionmentioning
confidence: 69%
“…Possibly illustrative of a network rather than a focal anti-epileptic effect is the more pronounced reduction in CPS compared to SPS following vertex stimulation in the study by Kinoshita et al, rather preventing the spread of aberrant activity within the brain than preventing epileptic activity from occurring at all [18]. A comparative review by Bae et al between 3 placebo-controlled studies did however identify superiority of targeted stimulation over nontargeted vertex stimulation (for review [61]; for separate RCTs [23,25,26]). Brighina et al explored the network approach by targeting the posterior cerebellar lobe with HF-rTMS and thereby addressing the cerebello-cortical network in order to induce diffuse inhibitory output to the cortex [14].…”
Section: Stimulation Protocolmentioning
confidence: 99%
“…all involved investigators is difficult to achieve and often poorly described. However, pooled data from placebo conditions in 3 RCTs estimated a relatively small placebo effect, with a mean SZF reduction of 0-2% and a responder rate of 16-20% across placebo conditions most likely attributable to normal SZF variability (for review [61]; for separate RCTs [23,25,26]). Since objective outcome parameters like the number of IEDs are less affected by placebo effects, inclusion in future study designs is encouraged.…”
Section: Interindividual Variabilitymentioning
confidence: 99%